2003
DOI: 10.1128/aac.47.11.3663-3666.2003
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Human Gentamicin Pharmacokinetics in an Experimental Enterococcus faecalis Endocarditis Model

Abstract: Significant differences between animal and human pharmacokinetics may be responsible for the conflicting results of experimental studies. This study determined the impact of human pharmacokinetic simulation (HPS) on gentamicin activity in an Enterococcus faecalis endocarditis model. The decrease in bacterial counts was greater with HPS than with a dose-equivalent regimen without HPS.Enterococcal organisms are a frequent cause of nosocomial infections (2,3,23,25,32,35). While a synergistic combination involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, using single-bolus injections completely overlooked the fact that most drugs have a much shorter half-life in rodents than in humans. Thus, it underestimated the importance of the more prolonged presence of antibiotics in the sera of humans (2,19,25,26). The critical importance of this aspect was demonstrated in further studies (5,7,8,11,23,24,40,46).…”
Section: Discussionmentioning
confidence: 96%
“…However, using single-bolus injections completely overlooked the fact that most drugs have a much shorter half-life in rodents than in humans. Thus, it underestimated the importance of the more prolonged presence of antibiotics in the sera of humans (2,19,25,26). The critical importance of this aspect was demonstrated in further studies (5,7,8,11,23,24,40,46).…”
Section: Discussionmentioning
confidence: 96%
“…This may indicate a slightly lower burst release of gentamicin upon application of the thermoresponsive HApN Gen than for the Collagen Gen. This is, however, difficult to verify as the half-life of gentamicin in the blood circulation of the rabbit is very short and accurate assessment of the pharmacokinetics with such few time-points is therefore a challenge [41,42]. Nevertheless, the peak plasma gentamicin levels measured in both groups are much lower than the commonly observed maximum concentration (C max ) of gentamicin in the human serum (18 lg/ml) upon intravenous administration of a conventional dose of 6 mg gentamicin/ kg body weight [43], indicating systemic toxicity is not a concern after application of either ALB.…”
Section: Discussionmentioning
confidence: 99%
“…dosing [92]. Despite this controversy, multiple doses are still recommended by guidelines, although such opposing results concerning the dosage of aminoglycosides in experimental IE might be due to significant differences between animal and human pharmacokinetics [93]. Moreover, a Danish group, in one of the most relevant contributions to EFIE treatment, recently demonstrated that q.d.…”
Section: R To Tetracyclinesmentioning
confidence: 98%